Evaluation of pH-modified chickpea protein isolate as a functional fat replacer in German-style cooked sausages - Kurmakova, Iryna; Lapytska, Nadiia; Novik, Hanna; Bondar, Olena; Vasylenko, Olha; Holovko, Tetiana; Zherebkin, Maksym; Levchenko, Iryna; Starynskyi, Oleh (Technology audit and production reserves, 2025)
The object of research is boiled German-type sausages with reduced fat content. The technological complexity of fat reduction in traditional meat emulsions is a major problem, which inevitably leads to a deterioration in both physicochemical parameters (emulsion stability) and sensory characteristics, such as texture and juiciness. This study was aimed at assessing the ability of chickpea protein isolate (CPI), modified using the pH-adjustment method, to act as a functional fat substitute. At the first stage, a comparison of the techno-functional properties of the modified isolate (solubility, WHC, OHC, EAI and ESI) with those of the native protein was carried out. All functional parameters of CPI were significantly improved by pH-treatment (p < 0.05). The solubility increased from 24.33% to 82.67%, and the emulsifying activity index (EAI) from 27.33 to 48.33 m²/g, which are significant changes for meat systems. For the experiment, modified CPI was introduced at concentrations of 1% (sample CPI1) and 2% (sample CPI2) for partial fat replacement. This was compared with the results of the high-fat control (23%). This combination allowed to significantly (p < 0.05) reduce the mass fraction of fat in the finished products. Sample CPI1 showed a decrease of 26.1%, and sample CPI2 showed a decrease of 40.6%. At the same time, the technological yield showed a clear trend towards growth (from 90.67% to 99.00%). Sensory analysis (on a 9-point scale) showed that sample CPI1 (1% CPI) had a sensory profile that was statistically indistinguishable (p > 0.05) from the control in all parameters, including taste (8.05 vs. 8.07) and aroma (7.63 vs. 7.78). However, sample CPI2 showed a significant deterioration in organoleptic properties (p < 0.05). Thus, pH-modified CPI proved its effectiveness as a fat substitute, and the 1% dosage was identified as the best method for preparing healthy cooked sausages without compromising on taste.